Astrotourism innovating for entrepreneurial excellence: enhancing user experiences and advancing astronomy education at KUSZA observatory, Universiti Sultan Zainal Abidin - Bely, Ahmad Hariz; Umar, Roslan; Sabri, Nor Hazmin; Mohd Nasir, Ahmad Lutfi Afifi (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Astrotourism is an emerging feature of science tourism that aims to foster an innovative and entrepreneurship through tourism for astronomical education with unique experiences. This aim to enhance the user experience alongside promoting astronomy as a learning tool for KUSZA Observatory. As a science tourism, it seeks to fill the gaps in astronomy education and low awareness of astrotourism. The innovation lies in encouraging technology of educational courses, sociological activities and environmentally tourism packages to provide teaching and learning behavior. The core activities are astronomy modules where students can use augmented reality and participate in guided stargazing sessions. This science communication complemented by tourism activities from observatory visits where the initiation comes from. The project makes positive input to the macroeconomics of the area by stimulating student’s interest in STEMs, creating jobs for the locals and expanding the tourism sector. From the environmental perspective, it advocates against excessive light pollution and promotes eco-friendly activities. The initiative has great potential for commercialization and can help KUSZA Observatory into a leading center of astrotourism, increasing inflow of tourists and raising scientific awareness. This invention embodies the convergence of education, tourism and entrepreneurship that brings a transformation both to the state and global levels.